Ethical Politics beyond Power: The Alawiyyin’s Moral Engagement and Non-Electoral Participation in Democratic Indonesia - Muflih, Abdullah Yusuf; Ajikontea, Haikal Akmal; Khotir, Tafrikhul (Jurnal Sosiologi Reflektif, 2025)
In Indonesia, debates around Islam and politics often revolve around tensions between secular democracy and religious identity, usually spotlighting mass-based movements or populist Islamism. However, the role of religious elites like The Alawiyyin—descendants of the Prophet Muhammad—remains understudied despite their subtle influence on political discourse. This study aims to examine how The Alawiyyin in Surakarta interpret Islamic politics and practice political participation without direct involvement in electoral processes. Employing a qualitative case study approach, it draws on data collected through semi-structured interviews, participant observation, and document analysis. The analysis uses triangulation techniques to ensure validity across multiple sources and methods. The study is framed by Bayat’s post-Islamism, Roy’s depoliticization thesis, Weber’s patrimonial authority, and Tilly’s concept of contentious politics. The findings indicate that for The Alawiyyin, politics is inherently ethical and inseparable from religious duty, where governance and leadership are regarded as moral responsibilities rather than instruments of power. Their participation is expressed through teaching, da’wah, and ethical dialogue, enabling them to influence civic and political values while maintaining independence from partisan agendas. The implication of this study is that Islamic political participation can extend beyond formal institutions, taking the form of ethical leadership and moral engagement that strengthen democratic pluralism in Indonesia. Di Indonesia, perdebatan tentang hubungan Islam dan politik sering berfokus pada ketegangan antara demokrasi sekuler dan identitas keagamaan, dengan sorotan utama pada gerakan massa atau Islamisme populis. Namun, peran elite agama seperti Alawiyyin—keturunan Nabi Muhammad—masih jarang dibahas meskipun mereka memiliki pengaruh halus dalam wacana politik. Penelitian ini bertujuan untuk mengkaji bagaimana komunitas Alawiyyin di Surakarta memahami politik dalam Islam dan bagaimana mereka terlibat dalam politik tanpa terlibat langsung dalam proses elektoral. Penelitian ini menggunakan pendekatan studi kasus kualitatif dengan data yang dikumpulkan melalui wawancara semi-terstruktur, observasi partisipatif, dan analisis dokumen. Analisis dilakukan dengan teknik triangulasi untuk menjaga validitas dari berbagai sumber dan metode. Penelitian ini menggunakan kerangka teori dari Bayat (post-Islamisme), Roy (depolitisasi Islamisme), Weber (otoritas patrimonial), dan Tilly (politik kontestasi). Hasil penelitian menunjukkan bahwa bagi komunitas Alawiyyin, politik tidak dapat dipisahkan dari etika keagamaan, di mana kepemimpinan dan tata kelola dipahami sebagai tanggung jawab moral, bukan sebagai sarana untuk meraih kekuasaan. Partisipasi politik mereka diekspresikan melalui pendidikan, dakwah, dan dialog etis yang memungkinkan mereka memengaruhi nilai-nilai sosial dan politik tanpa terikat pada kepentingan partai atau afiliasi politik tertentu. Implikasi penelitian ini adalah bahwa partisipasi politik Islam dapat melampaui batas-batas institusional formal dengan mewujud dalam bentuk kepemimpinan etis dan keterlibatan moral yang memperkuat pluralisme demokrasi di Indonesia.